Waiting for the Vanishing Shed - Phillips, D. Z. (Philosophy & theology, 1991)
An examination is offered of the claim that the possibility of religious belief is related to the possibility of lusus naturae, in the special sense of that phrase which many philosophers have adopted, in terms of its implications for the notion of the limits of intelligibility. The exposition includes a critical assessment of arguments offered by Peter Winch, R. F. Holland, Norman Malcolm, and H. O. Mounce.